Analysis of the Techno-Economic Competitiveness of a Three-Stage Membrane Separation Process for Biogas Upgrading Using a Biopolymer-Based Mixed-Matrix Membrane - Abejon-Elias, R (American Chemical Society, 2024)
The use of renewable energies and alternative fuels to replace fossil fuels is a goal for reducing greenhouse gas emissions. Biogas is a promising option to substitute natural gas, but adequate purification of the produced biogas is necessary (the CO2 content of raw biogas must be reduced). Membrane technologies have proven its technical viability to purify biogas until the defined requirements. Moreover, membranes based on biopolymers could reduce the environmental footprint of these purification processes. Nevertheless, due to the trade-off between purity and recovery, single-stage processes are not able to attain desired targets, so multiple stages are required to reach the desired high purities and recoveries. The aim of this study is to advance the use of biopolymer-based membranes for the separation of CO2/CH4 and evaluate the economic competitiveness of the designed multistage purification process. For this purpose, a chitosan composite membrane with organic (ionic liquid) and inorganic (titanosilicate) fillers in the selective layer was used to study the multistage configuration, considering CO2 and CH4 as both target products. The process configuration is based on three membrane units operating in series to enrich CO2 in the product stream from the permeate line, while the retentates are collected from each stage and mixed to obtain a CH4-rich stream in the retentate. The target objectives were purities and recoveries of ≥95% of CO2 in the permeate outlet and ≥97% of CH4 in the retentate outlet stream of the multistage process. The economic evaluation of the proposed three-stage separation process was performed for different process scales, from small installations to large plants (100-1000 N m3 h-1 feed flow rate basis), operated with two different pressure ratios (8 and 16). Total specific costs and contributions of the different cost terms to fixed and operating costs were estimated. Operating costs were the largest contributor to total costs in all of the scenarios studied. To highlight the total specific costs for the installations of 1000 N m3 h-1 capacity, the obtained total costs were 0.33 and 0.20 US $ N m3- for the 8 and 16 pressure ratio values, respectively. This latter cost was competitive when compared to the cost published in the literature. Moreover, a sensitivity analysis was performed to evaluate the effects of increased specific costs of materials (membrane cost) and energy (electricity cost) on the total specific costs of the three-stage separation process. © 2024 American Chemical Society.